An Assessment of Factors Undermining to Food Insecurity of Agriculture Households in Uttar Pradesh, India - Sitaram Bishnoi, Satyapriya, Sangeeta V., Lenin V, Sudipta Paul; Premlata Singh (Indian Journal of Extension Education, 2023)
The second most populous country in the world, India has enjoyed steady economic growth and has achieved self-sufficiency in grain production in recent years. Despite this, high levels of poverty, food insecurity and malnutrition persist. Around 21.25 per cent of the population lives on less than US1.90 a day, and levels of inequality and social exclusion are very high. For a country like India where the achievement of food security is a continuing challenge, the consequences of ignoring the problem of food and nutrition insecurity seem very dire. Food insecurity exists when all people, at all times, do not have physical and economic access to the sufficient, safe and nutritious food to meet their dietary needs and food preferences for an active and healthy life. First Millennium Development Goal states the target of “Halving hunger by 2015”. Sadly, the recent statistics for India present a very gloomy picture. We also put on the agenda the need to better understand the food insecurity in agriculture households in Uttar Pradesh. We conducted primary surveys in Bandha, Hamirpur and Sitapur districts in Uttar Pradesh to measure food insecurity with the Household Food Insecurity Access Scale (HFIAS). Altogether, 360 personal interviews and 6 FGD were conducted in three districts. The study shows that, Hamirpur and Sitapur are less likely affected by food insecurity than Bandha district. And also it was found that family size; monthly farm income and income spent on food are the main factors which are more likely to affect food insecurity.